Introduction [Filosofia: Revista da Faculdade de Letras da Universidade do Porto, vol.34, 2017] - Pereira, Paula Cristina (2017)
This issue follows on from the Philosophy of the City Conference 2017 (5th edition), organized by the Research Group Philosophy and Public Space of the Institute of Philosophy (R&DU 502), in partnership with the Philosophy of the City Research Group, held at the Faculty of Arts and Humanities, University of Porto, from 11th to 13th October. The event brought together a relevant international scientific community, with specialists from different branches of the Humanities and Social Sciences from 40 Portuguese and foreign universities. We are convinced that the multiplicity of approaches presented here poses a challenge and, simultaneously, an opportunity for the development and consolidation of research in this field of study.